1996
DOI: 10.1128/jcm.34.3.689-694.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Escherichia coli strains belonging to enteropathogenic E. coli serogroups isolated in Italy from children with diarrhea

Abstract: Fifty-five Escherichia coli strains belonging to enteropathogenic E. coli (EPEC) serogroups were examined for phenotypic and genetic factors associated with virulence. The strains were isolated in Italy from children with diarrhea and identified as EPEC by clinical laboratories using commercially available antisera. O:H serotyping showed that 35 strains (27 of O26, O111, and O128 serogroups) belonged to 11 serotypes considered to be classical EPEC O:H serotypes. The other 20 isolates were classified as 15 nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 44 publications
2
24
1
2
Order By: Relevance
“…EAF plasmids have been implicated in the initial adhesion of EPEC strains to intestinal mucosal surfaces [22], but data concerning the association between LA and EAF plasmids are varied. Results reported from Italy and UK [15,21] have shown low circulation of EAF plasmids among strains showing LA, whereas in a study conducted in Sao Paulo 100% association between LA and EAF had been observed [17]. In the present study this association was observed in 76% of the isolates, but similar to the data reported by Rosa et al [23] some LA strains were negative for all three genetic markers described for EPECs ( Table 2).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…EAF plasmids have been implicated in the initial adhesion of EPEC strains to intestinal mucosal surfaces [22], but data concerning the association between LA and EAF plasmids are varied. Results reported from Italy and UK [15,21] have shown low circulation of EAF plasmids among strains showing LA, whereas in a study conducted in Sao Paulo 100% association between LA and EAF had been observed [17]. In the present study this association was observed in 76% of the isolates, but similar to the data reported by Rosa et al [23] some LA strains were negative for all three genetic markers described for EPECs ( Table 2).…”
Section: Discussionsupporting
confidence: 87%
“…Comparison of the circulation rate of DNA sequences associated with A/E lesions and EAF plasmid in Italy [15] and those previously reported from UK [21] has led to the conclusion that eae might be a more suitable marker for epidemiological studies in Europe, while the EAF-related probe has been proposed as more appropriate for developing countries. However, in the present study in which isolates were classi¢ed, as EPEC on the basis of serogrouping and serotyping was not performed, no signi¢cant di¡erence between the circulation rate of EAF and eae sequences was observed (EAF = 44.4%, eae = 50%).…”
Section: Discussionmentioning
confidence: 82%
“…Serotype 026:H11 appears to be the predominant VTEC serotype of this serogroup, and isolations of this serotype have been reported from Germany (Bockemuhl et al 1992), Japan (Kudoh et al 1994), Australia (Goldwater and Bettelheim 1994) and the Czech Republic (Bielaszewska et al 1994(Bielaszewska et al , 1996 from cases of HUS. In addition, Thomas et al (1993Thomas et al ( , 1996 and Scotland et al (1988) in the United Kingdom reported cases of diarrhoea, bloody diarrhoea and HUS, and Pierard et al (1994and Pierard et al ( , 1997, Giammanco et al (1996), Huppertz et al (1996 and Czirok and Herpay (1995) reported cases of diarrhoea from Belgium, Italy, Germany, Hungary and Denmark, respectively. Caprioli and Luzzi (1995) and Farina et al (1996) reported cases of diarrhoea and HUS from Italy.…”
Section: The 026 Groupmentioning
confidence: 99%
“…As in groups 026 and 0111, the 0128 group has for many years been associated with EPEC Isolates of this group from human disease are predominantly of serotypes 0128:H-and 0128:H2. VTEC 0128:H-has been isolated from human cases of diarrhoea and HUS in Asia (Tamura et al 1996) andGermany (Bockemtihl et al 1992), and VTEC 0128:H2 has been isolated from cases of diarrhoea in Belgium (Pierard et al 1994(Pierard et al , 1997, Italy (Giammanco et al 1996), Japan (Kudoh et al 1994) and New Zealand (Brooks et al 1997). In addition, VTEC 0128:H7 has been isolated from a case of HUS in the United Kingdom (Thomas et al 1996), VTEC 0128:H8 from a case of diarrhoea in Asia (Tamura et al 1996) and VTEC 0128:H45 from a case of diarrhoea in the USA (Strockbine et al 1997).…”
Section: The 0128 Groupmentioning
confidence: 99%
“…The pathogenic ability of some of the classical EPEC serotypes has been demonstrated in several studies [5–7], and classical EPEC strains are well‐recognised as being diarrhoeagenic. However, their diarrhoeagenic potential cannot be inferred from the serotype itself, because strains belonging to the classical EPEC serotypes may not necessarily possess the virulence properties characteristic of EPEC [8–13]. Classical EPEC eae ‐positive O:H serotypes are grouped into typical EPEC, possessing a large virulence plasmid (the EPEC adherence factor (EAF) plasmid), and atypical EPEC (EAF‐negative) [14].…”
Section: Introductionmentioning
confidence: 99%